Hazard Potential Analysis at Banten 2 Steam Power Plant Using Job Safety Analysis (JSA) Method - Dewantari, Nustin Merdiana; Mariawati, Ade Sri; Alamsyah, Resky Noer; Umyati, Ani; Herlina, Lely; Sonda, Atia (Journal of Systems Engineering and Management, 2024)
Banten 2 Steam Power Plant is a crucial facility in electricity generation, utilizing steam as an energy source to drive turbines and produce electricity. The power generation process involves several key stages, where high-temperature steam is converted into mechanical energy and then into electricity through turbine rotation. In its operation, Banten 2 Steam Power Plant involves many workers with diverse working conditions and areas, making the level of risk and workplace accidents a primary concern. The Job Safety Analysis method is used to identify potential hazards in various areas such as firefighting areas, chimneys, and water treatment plants. The research findings indicate varying potential hazards, including risks of stumbling, slipping, trapping, scratching, exposure to flames, electric shock, and being struck by materials. Risk assessment shows high-risk levels: 5 for welding in the firefighting area, 4 for flue gas sampling, 5 for hydrant welding, and 3 for duplication and installation of membranes, cartridges, and vessel RO. Risk control is carried out through elimination, engineering, administrative controls, and the use of personal protective equipment (PPE).